(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article discusses the issues of improving the mechanism of deposit operations in Mikrokreditbank JSCB, the attractiveness of deposits, and the effectiveness of carrying out various attractive marketing reforms.